Academic stress and performance in first-year health sciences students in Chile: a cross-sectional study - Granada-Granada, Felipe; Valencia-Narbona, Martina; Lizana, Pablo A.; González-Rojas, Andrea (Frontiers in Psychology, 2025)
BackgroundAcademic stress can negatively influence academic performance, particularly in health science programs with high demands.ObjectiveTo analyze the association between perceived academic stress and academic performance in first-year kinesiology students, considering gender differences and stress dimensions (stressors, reactions, and coping strategies). Methods: This cross-sectional study included 82 students assessed using the SISCO-IIA inventory. Academic performance was measured via final course grades. Descriptive analyses, chi-square tests, t-tests, and binary logistic regression models were applied.ResultsStudents with high levels of academic stressors were significantly more likely to underperform (OR = 4.62, 95% CI [1.24, 17.22], p = 0.023). Female students reported higher emotional and behavioral responses to stress but were less likely to underperform (OR = 0.30, 95% CI [0.11, 0.79], p = 0.014). Age was not significantly associated with performance (p = 0.433).ConclusionAcademic stress negatively influences academic outcomes among first-year students. Gender differences in stress response patterns may affect vulnerability and coping effectiveness. These findings highlight the need for early screening, targeted interventions, and support systems to mitigate academic stress and promote student success.